(untitled) (Dimensión Empresarial, 2019)
This literature review on Social Responsibility presents it to manage the social and environmental impacts caused by an organization. For this reason, it is a priority to understand in this management approach the commitment that the organization acquires and its directives, the development of socially responsible management strategies and harmonized with responsible practices, and, finally, how to measure social and environmental performance. In this sense, indicators for socio-environmental performance in organizations are proposed; harmonized with the Sustainable Development Goals. As a result, an adjustable scoreboard is built for the activities of any organization.